A review of the utilisation of natural gas with high carbon dioxide content as automotive fuel in an indirect injection diesel engine - Opatola, R.A. (EDP Sciences, 2014)
The persistent consumption of fossil fuels by modern transportation tends toward feared depletion in crude oil and infliction of health risks on human beings and the environment due to the noxious emissions from the combustion of fossil fuels. This work examines the prospects of fuel modification in improving engine performance by utilising compressed natural gas (CNG) mixed with varying proportions of carbon dioxide (CO2) as fuel in Diesel engines. The extent to which the addition of CO2 to CNG could help simulate the effects of exhaust gas recirculation (EGR) as employed in modern engine technology will be established. Â© 2014 Owned by the authors, published by EDP Sciences.